The Influence Of Transformational Leadership Style And Motivation For Employee Performance By Communication Quality As A Variable Intervening In The Employment Service General And Spatial Planning Asahan Regency - Sujarwo; Mesra B; Abdi Sugiarto (International Journal of Management, Economic and Accounting, 2025)
This study aims to examine the influence of transformational leadership style and motivation on employee performance, as well as the role of communication quality as an intervening variable. This type of research is quantitative associative causal, carried out at the Office of Public Works and Spatial Planning of Asahan Regency from September to November 2024, with the entire employee population of 145 people as a sample. The data analysis technique uses Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS 3.0 software. The results showed that transformational leadership style and motivation had a positive and significant influence on employee performance, with T-statistical values of 4.265 and 6.718 and P-values of 0.000 < 0.05, respectively. Transformational leadership style also has a significant influence on the quality of employee communication (T-statistic 6,428), as well as motivation (T-statistic 3,851), which means that improved leadership and motivation can improve the quality of communication. However, the quality of communication had no significant influence on employee performance (T-statistic 1.342, P-value 0.182 > 0.05) and was unable to intervene in the relationship between transformational leadership style and motivation on employee performance, with T-statistical values of 1.372 and 1.114, respectively. The implication of these findings is that employee performance improvement is more effectively achieved through a focus on developing transformational leadership styles and motivation, without relying on communication quality as an intermediary factor. This study recommends that institutions focus more on leadership strategies and motivation that directly impact performance to achieve optimal results.